O desenvolvimento do vínculo mãe-bebê no sistema prisional brasileiro - Costa, Camila Casé da (Universidade Federal de São Carlos, 2022)
In Brazil, with the increase of the female prison population by 267.8%, over almost twenty years, questions arise about the particularities of this public and what involves the lives of women in prison. One of them is motherhood, since more than half of them have children and this implies, in most cases, separation and bond breaking. Outside prison bars, mothers are most often configured as primary caregivers and their absence weakens family relationships; inside them, there are lonely mothers, with ambivalent and guilty feelings, and who may also be, for a short time, in the presence of a baby, whether during pregnancy or postpartum, experiencing a hyperbolic version of the motherhood. Given this, it was intended to investigate the experience of becoming a mother behind bars and to analyze the variables involved in the process of gestating, giving birth and living with the child in this environment, such as its implications for the formation of the mother-baby bond. Three woman incarcerated in a female penitentiary in the state of São Paulo participated. Two interviews were carried out by videoconference with each participant, one during their pregnancy and one in the postpartum period, in addition to applying the Questionnaire on Burdening Experience at this first moment. Through the qualitative analysis of the data obtained, similarities and differences in the exercise of motherhood of the participants in the prison environment were perceived. Regarding the similarities, the prison history, the adverse experiences of emotional abuse and emotional neglet, and the large number of mentions to the family support and the suffering resulting from the imprisonment and separation of the baby stand out. The differences were in the life story, in the experiences of physical abuse and in the decision about the moment of separation. From the analysis of the data obtained in this research, it was expected to be produce additional scientific knowledge about the theme of motherhood in Brazilian prisons, which can contribute to further intervention projects development for this target population.
The development of the mother-baby bond in the Brazilian prison system
Keywords: Gestação; Maternidade; Mulheres; Prisão; Pós-parto; Vínculo; Gestation; Motherhood; Women; Prision; Postpartum; Bond; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA